Temporal Bone Fracture Causing Superior Semicircular Canal Dehiscence. (10th September 2014) - Peng, Kevin A.; Ahmed, Sameer; Yang, Isaac; Gopen, Quinton
Abstract : Importance . Superior semicircular canal dehiscence (SCD) is a third window lesion of the inner ear causing symptoms of vertigo, autophony, tinnitus, and hearing loss. A "two-hit" hypothesis has traditionally been proposed, whereby thinly developed bone overlying the superior canal is disrupted by a sudden change in intracranial pressure. Although the symptoms of SCD may be precipitated by head injury, no previous reports have described a temporal bone fracture directly causing SCD. Observations . Two patients sustained temporal bone fractures after closed head trauma, and developed unilateral otologic symptoms consistent with SCD. In each instance, computed tomography imaging revealed fractures extending through the bony roof of the superior semicircular canal. Conclusions and Relevance . Temporal bone fractures, which are largely treated nonoperatively, have not previously been reported to cause SCD. As it is a potentially treatable entity, SCD resulting from temporal bone fracture must be recognized as a possibility and diagnosed promptly if present.